Systemic and Gastrohepatic Mucormycosis in Dogs. (February 2020) - Alves, R.C.; Ferreira, J.S.; Alves, A.S.; Maia, L.A.; Dutra, V.; Souza, A.P.; Galiza, G.J.N.; Dantas, A.F.M.
Summary: We describe two cases of mucormycosis with systemic and gastrohepatic involvement in two male poodles. Respiratory, neurological and gastrointestinal signs progressed to death within 3 and 19 days of the onset of clinical signs, respectively. In case 1, there was systemic disease affecting the lungs, heart and brain. The lesions were characterized by yellow or red, raised, irregular areas that extended into deeper tissue from the surface. In case 2, there was gastric rupture; the margins of the rupture and the gastric mucosa were covered by a thick, white, friable material. In the liver, there were multiple yellow–white cavitated nodules. Histologically, pyogranulomas occurred in the affected organs and were associated with vasculitis, thrombosis and fungal hyphae. The diagnosis of mucormycosis was based on the characteristic microscopical lesions together with the morphology and staining features of the fungus. The hyphae were strongly labelled by monoclonal antibody specific for Rhizopus arrhizus on immunohistochemistry. Underlying immunosuppression was suspected in both cases.